Operational Standards Preparation Workshop for Master Program at FKIP UNTAN - Y. Touvan Juni Samodra; Sri Buwono; Eka Aryati; Edi Yusmin (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2020)
The purpose of this activity was to provide standard operating procedures (SOP) for master program at FKIP. The availability of absolute SOP must exist for the sake of smooth operation and to ensure that every activity takes place in an organized manner. PKM activities were carried out with workshops between the quality assurance unit as a drafter, lecturers in the S2 study program, the Faculty publishing unit, and staff. The result of the activity was the availability of SOP documents for master program, attended by 30 participants. The activities' results were SOP related to monitoring and evaluation of the design and research of the thesis, monitoring and evaluation of the thesis guidance process, monitoring and evaluating the thesis supervisor, and monitoring and evaluating the thesis exam.